ANALISIS KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 3 NGERANGAN DALAM PEMBELAJARAN BAHASA INDONESIA - Ambarsari, mei; Grahito Wicaksono, Anggit; Sarafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early reading skills are an important foundation in the literacy process that must be mastered by elementary school students, especially in lower grades. However, the reality in the field shows that many second-grade students still experience reading difficulties, such as mispronunciation, inappropriate intonation, and low reading comprehension. This study aims to describe the early reading skills of second-grade students at SDN 3 Ngerangan and identify the factors influencing them. The study employs a descriptive qualitative approach using a case study method. Data were collected through observation, interviews, documentation, and oral tests administered to 20 students, as well as teachers and parents. The results of the study indicate that some students are in the low reading ability category, characterized by difficulties in voice clarity, pronunciation of combined letters, use of intonation, and application of punctuation marks. The identified inhibiting factors include low reading interest, lack of self-confidence, minimal parental involvement, and limited reading materials at home. It is recommended that teachers develop enjoyable and varied reading instruction methods, while parents are encouraged to increase their involvement in children’s reading activities to support early literacy development.